Influence of coal gangue mulching with various thicknesses and particle sizes on soil water characteristics - Xiu-Na Han (Nature Portfolio, 2021)
Abstract Water availability seriously affects vegetation restoration in arid mining areas, and mulching is an effective way to improve soil water conditions. Coal gangue occupies large swathes of land resources, resulting in ecological fragility and various environmental problems. Despite coal gangue having mineral elements similar to those in soil, its potential function as a mulch for soil water conservation has been unclear. Herein, mulching on the surfaces of soil columns with 30 cm height and 15 cm inner diameter was conducted using coal gangue with four particle size ranges (0–0.5, 0.5–1, 1–2, and 2–4 cm) and four thicknesses (4, 8, 12, and 16 cm) under laboratory conditions to investigate water infiltration and evaporation under different conditions. The cumulative infiltration of the treatments with mulching thicknesses of 4 cm (T1), 8 cm (T2), 12 cm (T3), and 16 cm (T4) was 16.1%, 22.9%, 28.6%, and 41.6% greater than that of the control, respectively. The cumulative evaporation of the treatments with particle size ranges of 0–0.5 cm (P1), 0.5–1 cm (P2), 1–2 cm (P3), and 2–4 cm (P4) was 6.5%, 28.6%, 22.9%, and 18.6% lower than the control, respectively. Overall, to enhance the soil water storage capacity in mining areas, the results suggest that coal gangue mulching with a thickness of 8–16 cm and particle size range of 0.5–2 cm is suitable.